Streptococcus dysgalactiae subsp.-equisimilis as an emerging secondary pathogen in leprosy foot ulcers - Kumar Ebineshan; Michael Sukumar Pallapati; Aparna Srikantam (Iranian Journal of Microbiology)
Background and Objectives: Leprosy foot ulcers (LFU) tend to become chronic due to secondary bacterial infections, leading to subsequent disfigurement and disability. Treatment modality for infected plantar ulcers thus so far is majorly based on conventional approach of empirical antibacterial therapy. However, this approach tends to overlook unconventional pathogens which are likely to be present in the LFU. Materials and Methods: Twenty-six leprosy patients (17 males and 9 females) who had completed multidrug therapy (MDT) and those are suffering from foot ulcer were included. Using sterile cotton swabs, two wound swabs were collected, of these; one for bacterial culture and another for NGS (Next Generation Sequencing). Results: Out of 26 samples tested on conventional bacterial culture, Streptococcus spp. (50%) was predominant organism. On NGS, 09/26 (34.61%) showed Streptococcus-dysgalactiae-subsp.-equisimilis-GGS 12 as the most abundant single organism, along with some unknown and unclassified organisms; 03/26 (11.5%) were Arcanobacterium-haemolyticum-DSM-20595 alone and 02/26 (7.69%) were Streptococcus-pyogenes alone. A combination of Arcanobacterium-haemolyticum-DSM-20595 and Streptococcus-dysgalactiae-subsp.-equisimilis-GGS 124 was found in nine (34.61%) specimens. Conclusion: Polymicrobial infection with conventional and unconventional pathogenic bacteria is another notable finding suggesting appropriate interventions. The study findings also reiterate the need for understanding the polymicrobial infections and their role in the clinical progression of the LFU.